2020
DOI: 10.3386/w27378
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic Factors Associated with Self-Protecting Behavior during the Covid-19 Pandemic

Abstract: Disease spread is in part a function of individual behavior. We examine the factors predicting individual behavior during the Covid-19 pandemic in the United States using novel data collected by Belot et al. (2020). Among other factors, we show that people with lower income, less flexible work arrangements (e.g., an inability to tele-work) and lack of outside space at home are less likely to engage in behaviors, such as social distancing, that limit the spread of disease. We also find evidence that region, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
132
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(147 citation statements)
references
References 12 publications
(13 reference statements)
10
132
4
1
Order By: Relevance
“…While a fatalistic message arguing that the pandemic is unstoppable and that mitigation efforts may do more harm than good increased fatalism, an optimistic message that drew attention to the effectiveness of coping efforts and collective connectedness in times of need reduced fatalism. Furthermore, several recent studies reported that more fatalistic beliefs about the infectiousness of COVID-19 were less likely to comply with preventive measures (55,56). In Israel, however, higher fear of COVID-19 was unrelated to fatalism, which differs from the findings in the Swiss sample as well as the US sample of Hayes and Clerk (54).…”
Section: The Role Of Fatalismmentioning
confidence: 76%
“…While a fatalistic message arguing that the pandemic is unstoppable and that mitigation efforts may do more harm than good increased fatalism, an optimistic message that drew attention to the effectiveness of coping efforts and collective connectedness in times of need reduced fatalism. Furthermore, several recent studies reported that more fatalistic beliefs about the infectiousness of COVID-19 were less likely to comply with preventive measures (55,56). In Israel, however, higher fear of COVID-19 was unrelated to fatalism, which differs from the findings in the Swiss sample as well as the US sample of Hayes and Clerk (54).…”
Section: The Role Of Fatalismmentioning
confidence: 76%
“…To explore the spreading of COVID-19 in relation to population density, this study included potential confounding population characteristics: a) older age, as older people are said to be more susceptibility to COVID-19 6 and are more likely to live in less densely populated areas; 7 b) ethnicity, as ethnic minorities are overrepresented among COVID-19 cases 8,9 and are more likely to live in more densely populated areas; 7 c) higher occupational classes, as these people may have more flexible work arrangements, allowing them to better cope with the restrictions, 10 and are more likely to live in cities. 7 Population characteristics included as co-variates are d) healthier populations, and e) the COVID-19 prevalence rate per 100 000 people on March 15.…”
Section: Methodsmentioning
confidence: 99%
“…For these tasks, population-representative estimates are essential. While we focus on disparities in preexisting health conditions and their implications for vulnerability to severe complications, our work is a complement to studies of disparities in exposure to the coronavirus (25)(26)(27) and in inequities in health care (24,28,29).…”
mentioning
confidence: 99%